Causes and differentials of childhood mortality in Iraq - Salman Khawla; Majeed Faiza A; Al-Ward Nada J; Ali Mohamed M; Awqati Naira A; Al-Alak Mahdi; Al-Gasseer Naeema (BMC, 2009)
Abstract Background Limited information is available in Iraq regarding the causes of under-five mortality. The vital registration system is deficient in its coverage, particularly from rural areas where access to health services is limited and most deaths occur at home, i.e. outside the health system, and hence the cause of death goes unreported. Knowledge of patterns and trends in causes of under-five mortality is essential for decision-makers in assessing programmatic needs, prioritizing interventions, and monitoring progress. The aim of this study was to identify causes of under-five children deaths using a simplified verbal autopsy questionnaire. The objective was to define the leading symptoms and cause of death among Iraqi children from all regions of Iraq during 1994-1999. Methods To determine the cause structure of child deaths, a simplified verbal autopsy questionnaire was used in interviews conducted in the Iraqi Child & Maternal Mortality Survey (ICMMS) 1999 national sample. All the mothers/caregivers of the deceased children were asked open-ended questions about the symptoms within the two weeks preceding death; they could mention more than one symptom. Results The leading cause of death among under-five children was found to be childhood illnesses in 81.2%, followed by sudden death in 8.9% and accidents in 3.3%. Among under-five children dying of illnesses, cough and difficulty in breathing were the main symptoms preceding death in 34.0%, followed by diarrhea in 24.4%. Among neonates the leading cause was cough/and or difficulty in breathing in 42.3%, followed by sudden death in 11.9%, congenital abnormalities in 10.3% and prematurity in 10.2%. Diarrhea was the leading cause of death among infants in 49.8%, followed by cough and/or difficulty in breathing in 26.6%. Among children 12-59 months diarrhea was the leading cause of death in 43.4%, followed by accidents, injuries, and poisoning in 19.3%, then cough/difficulty in breathing in 14.8%. Conclusion In Iraq Under-five child mortality is one of the highest in the Middle East region; deaths during the neonatal period accounted for more than half of under-five children deaths highlighting an urgent need to introduce health interventions to improve essential neonatal care. Priority needs to be given to the prevention, early and effective treatment of neonatal conditions, diarrheal diseases, acute respiratory infections, and accidents. This study points to the need for further standardized assessments of under-5 mortality in Iraq.